HTML5 game development insights - McAnlis, Colt (Expert's voice in game development., 2014)
HTML5 Game Development Insights is a from-the-trenches collection of tips, tricks, hacks, and advice straight from professional HTML5 game developers. The 24 chapters here include unique, cutting edge, and essential techniques for creating and optimizing modern HTML5 games. You will learn things such as using the Gamepad API, real-time networking, getting 60fps full screen HTML5 games on mobile, using languages such as Dart and TypeScript, and tips for streamlining and automating your workflow. Game development is a complex topic, but you don't need to reinvent the wheel. HTML5 Game Development Insights will teach you how the pros do it. The book is comprised of six main sections: Performance; Game Media: Sound and Rendering; Networking, Load Times, and Assets; Mobile Techniques and Advice; Cross-Language JavaScript; Tools and Useful Libraries. Within each of these sections, you will find tips that will help you work faster and more efficiently and achieve better results. Presented as a series of short chapters from various professionals in the HTML5 gaming industry, all of the source code for each article is included and can be used by advanced programmers immediately.